Biogeographic variation in the baboon: dissecting the cline. Issue 4 (29th August 2013) - Dunn, Jason; Cardini, Andrea; Elton, Sarah
Abstract: All species demonstrate intraspecific anatomical variation. While generalisations such as Bergman's and Allen's rules have attempted to explain the geographic structuring of variation with some success, recent work has demonstrated limited support for these in certain Old World monkeys. This study extends this research to the baboon: a species that is widely distributed across sub‐Saharan Africa and exhibits clinal variation across an environmentally disparate range. This study uses trend surface analysis to map the pattern of skull variation in size and shape in order to visualise the main axes of morphological variation. Patterns of shape and size‐controlled shape are compared to highlight morphological variation that is underpinned by allometry alone. Partial regression is used to dissociate the effects of environmental terms, such as rainfall, temperature and spatial position. The diminutive Kinda baboon is outlying in size, so analyses were carried out with and without this taxon. Skull size variation demonstrates an east–west pattern, with small animals at the two extremes and large animals in Central and Southern Africa. Shape variation demonstrates the same geographical pattern as skull size, with small‐sized animals exhibiting classic paedomorphic morphology. However, an additional north–south axis of variation emerges. After controlling for skull size, the diminutive Kinda baboon is no longer an outlier for size and shape. Also, the east–west component is no longer evident and discriminant function analysis shows an increased misclassification of adjacent taxa previously differentiated by size. This demonstrates the east–west component of shape variation is underpinned by skull size, while the north–south axis is not. The latter axis is explicable in phylogenetic terms: baboons arose in Southern Africa and colonised East and West Africa to the north, diverging in the process, aided by climate‐mediated isolating mechanisms. Environmental terms appear poorly correlated with shape variation compared with geography. This might indicate that there is no simple environment–morphology association, but certainly demonstrates that phylogenetic history is an overbearing factor in baboon morphological variation.